Perceptual-cognitive skills and talent development environments in soccer: A scoping review. - Andrew O Triggs; Joe Causer; Allistair P McRobert; Matthew Andrew (PLoS ONE)
Perceptual-cognitive skills are a key performance component within professional soccer. Consequently, their role within talent development environments has gained increasing attention. Despite this growing interest, research linking perceptual-cognitive skills to the talent development process remains relatively limited. The present study provided a scoping review examining perceptual-cognitive skills within soccer-specific environments within the last three decades, with a particular focus on outcomes relevant to talent development contexts. Following PRISMA guidelines, specific inclusion and exclusion criteria were set, where 55 studies were included in the final review. Narrative analysis identified key themes in the literature, including visual search behaviours, cognitive capabilities, performance, and methodologies. These themes are discussed with areas for future research identified to support the work of stakeholders in talent development contexts (e.g., coaches, scouts, academy directors), to re-direct future research efforts to further bridge the gap between science and application.